4. INTEGRATION OF IMMIGRATION ADMINISTRATION AND NATIONALPOLICE INFORMATION SYSTEMS TO ENHANCE SERVICE QUALITY - Nabila Nasywa Armita Siahaan; Pascalis Danny Kristi Wibowo; Rita Kusuma Astuti; Nur Priyanto; Suroso; Anwar Hendro; Tutidikatama; Hendri Himawan; Ida Farida (Jurnal TNI Angkatan Udara, 2026)
This study aims to analyze how the integration of the Immigration AdministrationInformation System and the information system of the Indonesian National Police can improveservice quality. The increasing intensity of human activities and cross-border mobility requiresthe state to ensure immigration services are fast and precise. These services are also expectedto be accurate and secure to support supervision when dealing with immigration-related risks.This study was initially conducted based on the finding that inter-agency coordination remainssuboptimal and that the existing regulations are not yet sufficiently appropriate. Therefore, thestudy employed a qualitative approach using a literature review method based on 15 scientificarticles. The data were analyzed through content and thematic analysis before the finalconclusions were drawn. The findings show that the proper integration of immigration and policeinformation systems can improve inspection accuracy and strengthen service coordination. Theanalysis also confirms that successful integration does not depend solely on technology, butalso requires attention to several elements, including appropriate regulations and the accuracyof officers in carrying out their duties. In addition, cybersecurity measures are needed to preventdata breaches and unauthorized access. Based on these findings, it can be concluded thatinformation system integration is a strategic step toward achieving immigration services that aremore effective, efficient, and accountable.